1993
DOI: 10.1084/jem.178.6.2007
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin gamma 2b transgenes inhibit heavy chain gene rearrangement, but cannot promote B cell development.

Abstract: SummaryTransgenic mice with a y2b transgene were produced to investigate whether y2b can replace P in the development of B lymphocytes . Transgenic y2b is present on the surface of B cells. Young transgenic mice have a dramatic decrease in B cell numbers, however, older mice have almost normal B cell numbers . Strikingly, all y2b-expressing B cells in the spleen also express h . The same is true for mice with a hybrid transgene in which the A. transmembrane and intracytoplasmic sequences replace those of y2b (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…However, the expression of the transmembrane form of introduced Ig transgenes does not necessarily prevent DNA rearrangement of the endogenous loci to secure allelic exclusion (56 -58). It has also been shown that ␥2b transgenes are coexpressed with endogenous , and that ␥2b cannot by itself promote B cell development in the KO background (40,55,59). The few mature B cells that do develop in the transgenic mice express both endogenous and transgenic ␥2b, and in addition, L chain is expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression of the transmembrane form of introduced Ig transgenes does not necessarily prevent DNA rearrangement of the endogenous loci to secure allelic exclusion (56 -58). It has also been shown that ␥2b transgenes are coexpressed with endogenous , and that ␥2b cannot by itself promote B cell development in the KO background (40,55,59). The few mature B cells that do develop in the transgenic mice express both endogenous and transgenic ␥2b, and in addition, L chain is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pre-B cell development could be facilitated by VDJ recombination and endogenous H chain expression (, or ␦ in the MT mice) initially accompanied but later replaced by transgene expression. It has been shown that the introduction of a rearranged murine ␥ transgene does not promote B cell development because joint expression with endogenous is required (40,41). This finding suggested that IgG could not replace IgM, and it was speculated that their feedback signals to control B cell maturation must be different.…”
Section: H Chain-only Abs Are Equally Well Expressed In C H Locus Delmentioning
confidence: 99%
“…RNA probes. The antisense riboprobe for gpt was generated from a subclone of pHRD, for C from C-2 (35), and for GAPDH from a cloned PCR product amplified from a mouse pre-B-cell library (36) with primers generously supplied by N. Hay (University of Chicago). The V167 (Ig light-chain variable region gene segment utilized by the MOPC-167 myeloma) riboprobe was generated from pGEMV167 (38).…”
Section: Methodsmentioning
confidence: 99%
“…First-strand cDNA was synthesized using M-MLV Reverse Transcriptase (Promega, Madison, WI) and oligodeoxythymidine [oligo(dT) 20 ] primers. The two IGHM genes expression assays were performed using LightCycler 480 SYBR Green I Master mix (Roche, Basel, Switzerland) with primers to GAPDH (For: 59-AGA TGG TGA AGG TCG GAG TG-39; Rev: 59-GAA GGT CAA TGA AGG GGT CA- Fluorescence in situ hybridization analysis BAC DNA was isolated using a QIAGEN Large-Construct Kit (Qiagen, Valencia, CA) according to the manufacturer's protocols.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…This process is not confined solely to allelic genes located on homologous chromosomes; it also regulates the activity of IgH genes located on different chromosomes. A number of studies using transgenic mice have revealed that the expression of exogenous transgenic IgH genes could cause a strong inhibition of endogenous IgH genes and disordered B cell development (17)(18)(19)(20). Thus far, cattle are the only mammalian species reported to have two functional IgH loci on different chromosomes, and it remains unclear how these two gene loci interact when expressed.…”
mentioning
confidence: 99%